Systemic immune response development in Albino rats after retrograde instillation of COVID-19 vaccine to submandibular salivary gland: An experimental study - Wafaa Yahia Alghonemy; Mai Badreldin Helal (Elsevier, 2022)
Objective: This study aimed to investigate whether using the submandibular gland duct (SMD) as an alternative mucosal route for vaccine administration induced anti-COVID-19 specific immunity. Material and methods: Forty rats were randomized equally into four groups; Group I: Rats did not receive any intervention. Group II: Rats were subjected to intramuscular (IM) injection of COVID-19 vaccine. Group III: Rats were subjected to ductal cannulation by retrograde instillation of sterile saline into right SMD. Group IV: Rats in this group who had 0.5 ml of COVID-19 vaccine retrogradely injected into the right SMD. Subsequently, rats were examined for anti-COVID-19 specific antibodies (IgG). Also, light microscopic observation of glandular changes and immunohistochemical staining for CD20 was performed. Results: The obtained results demonstrated a significant increase in anti-COVID-19 IgG levels in all rats vaccinated via intraductal immunization (group IV) compared to group II. Histologically, ectopic follicles were found within the glandular lobules of the inoculated submandibular gland (SMG) in group IV. In addition, the nearby lymph node in group IV demonstrated reactive follicle characteristics in the form of activated secondary follicles with germinal centers (GCs). Immunohistochemically, CD20 was localized in group IV in GCs of the ectopic lymphoid tissue and the nearby lymph nodes while group I, group II, and III demonstrated negative immunoreactivity. Conclusion: The immune response demonstrated by intraductal SG immunization is generally more significant than that elicited by IM inoculation of the same vaccine.